Nanostructural crystallization of metals - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Based on thermodynamic calculations, it is shown that metal crystallization is an equilibrium nanostructural process. At the beginning, trigonal or tetragonal structure-forming nanocrystals are formed from elementary nanocrystals. Then crystallization centers are formed from them. Further, tetragonal or hexagonal dendrites are formed from them and tetragonal or trigonal structure-forming nanocrystals. Their forms depend on the degree of branching of dendrites. The most branched of them (compact dendrites) are tetragonal or hexagonal crystals.